Kebijakan Jepang di Kawasan Asia Tenggara melalui Penandatanganan “Joint Declaration on AJCEP” di Era Kepemimpinan Junichiro Koizumi - Fitri, Nafira; Sushanti, S.S., M.Si., Sukma; Kawitri Resen, S.IP., M.A, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2014)
ABSTRAK This paper found that the making of Japanese foreign policy related to trade sector in Southeast Asia in the era of the leadership of Junichiro Koizumi. This topic is interesting, because until the mid-1990s, Japan committed to making the policy of multilateralism and reject the free trade agreements, because they assume the free trade agreement is not in accordance with the GATT / WTO. But in the era of Junichiro Koizumi changed the emphasis of economic cooperation to